FUNDAMENTAL CHARACTERISTICS OF RELIABILITY IN TECHNOLOGICAL PROCESSES IN FERROUS METAL INDUSTRY - Kazhikenova S. Sh.; Belomestny D. (Scientific Journal of Pedagogy and Economics, 2019)
Problems of reliability in the areas of metal industry are of the most immediate interest. The efficiency of using the different technological schemes is closely connected with ensuring the required accuracy, productivity and operational economy which are mostly defined by the degree of their reliability. The decisive influence on the perfection of technological processes has the level of scientific support, because on the stage of scientific researches the potential of innovations, which is materialized through design and construction work into production, is laid. The purpose of this work – to develop mathematical and computational models for assessment the reliability of fundamental characteristics in technological processes in the areas of non-ferrous and ferrous metal industry with the aim of achieving the required quality of output. The suggested strategy of quantitative and qualitative assessment of reliability on the basis of fundamental conservation laws on maximum entropy will provide the prevention of errors on the stage of scientific elaboration in order to avert the appearance of defect or remove it without bringing it into a final stage of production, which is extremely important in the countries with market-oriented system of controlling the technology level and quality. The application of ruggedness analysis technology in technological output and processes offered in this work will lead to improved production method and considerable reduction in expenditure on production of this output, improvement in quality and competitive capability. The novelty of the thesis consists in that for the forts time to the analysis of the technology of chemical-and-metallurgical processes and schemes there will be applied objective and fundamental information criteria expressed in universal units, i.e. bits. Methods of computer modeling have been developed for calculation of fundamental characteristics of production in a way of refinement the cast iron technological schemes reliability. Methods of computer modeling have been developed for calculation of fundamental characteristics of in production in a way of direct receiving iron technological schemes reliability.